Development of a higher order thinking teaching model for basic education students in Science / Gulistan Ahmed Mohammed Artosh - Gulistan Ahmed, Mohammed Artosh (2016)
The purpose of the study was to develop a higher order thinking (HOT) teaching model for science among basic education students. The development of the model was aimed at overcoming basic students’ needs in terms of developing their higher cognitive skills in science education. The study adopted the Design and Development Research Approach. Based on the approach, the study was conducted in three phases namely, needs analysis, design and development and evaluation phase. In order to identify the needs to develop the model, two instruments were used in phase1. First, a Higher Order Thinking Level Test (HOTLT) was developed based on the Bloom’s taxonomy of the cognitive domain and consisted of 25 multiple choice questions. The test was distributed to a randomly chosen sample comprising 418 7th grade students in the Iraqi-Kurdistan region. Second, a Strategy Use Survey Questionnaire (SUSQ) was developed to investigate the strategies used by 7th grade science teachers in science. The questionnaire consisted of 31 questions with a 5-point Likert scale and distributed among 212 7th grade science teachers in the Iraqi-Kurdistan region. Data for this phase were analyzed using descriptive statistics via the SPSS program. Phase 2 adopted the Fuzzy Delphi Method (FDM) to develop the model via a panel of 20 experts. The model was developed based on the experts’ responses to a seven-Likert linguistic scale survey questionnaire. The threshold value (d) was calculated to determine the experts’ consensus for all questionnaire items, while the alpha-cut value > 0.5 was used to select the elements. The ranking process was used to identify the priority of elements for implementation in science class. Phase 3 adopted the partial least square (PLS-SEM) approach to evaluate the model. The evaluation was carried out via 318 science teachers. A two-stage process was employed whereby the measurement model was evaluated followed by an evaluation of the structural model. ii The overall findings for phase 1 revealed that majority of the 7th grade students were at a lower level of thinking skills (LOT). The findings also indicated that a variety of HOT teaching strategies were lacking among science teachers and that low processing strategies, such as focusing on students’ memorizing of basic concepts were dominant among them. Thus, the findings necessitated the study to develop the model. Findings from phase 2 using FDM resulted in the development of the model that consisted of 5 main stages and 24 sub-stages as the activities that engage basic education students in using their higher cognitive skills in science. Finally, through running factor analysis and PLS evaluation, the findings from phase 3 showed that the HOT teaching model consisted of overall 5 stages and 17 sub-stages that have a positive significance influence on students’ HOT (